Experimental investigation on stability and thermal conductivity of SiO2 nanoparticles as green nanofluids for application thermal system - Ramadhan, Anwar Ilmar; Umar, Efrizon; Hendrawati, Tri Yuni; Sari, Alvika Meta; Rahardja, Istianto Budhi; Aziz, Azmairit; Firmansyah, Firmansyah; Yulianto, Sulis; Azmi, Wan Hamzah (SINERGI, 2024)
In the last few years, much research has focused on the stability and improvement of the thermo-physical properties of single-component nanofluids. Some studies have not made many improvements to the stability and thermophysical properties of various types of green nanofluids from several variations of nanoparticles. Green nanofluids must be developed to improve heat transfer performance from their stability and thermal conductivity factors. Stability and thermal conductivity of Nano-silicate suspended in a base mixture of water /ethylene glycol with the ratio of 60:40, different volume concentrations were investigated. The experiments carried out were the stability of the green nanofluids investigated for volume concentrations of 0.1~0.3% and temperature conditions from 30 to 70°C for thermal conductivity measurement using TEMPOS Thermal Properties Analyzer. The experimental results showed that the stability analysis of the green nanofluids prepared by the UV-Vis method was stable up to 30 days after preparation with a sonication time of 1 hour with a ratio of 70-80%. The evaluation of the zeta potential for green nanofluids obtained a value of 33.57 mV with a moderate stability classification. The highest thermal conductivity for the green nanofluids was obtained at 0.3%, and the maximum increase was 17% higher than that of the base liquid (W/EG). Green nanofluids with a concentration of 0.1% gave the lowest effective thermal conductivity of 1.09 time at 70°C.